Metabolites in the milk of buffalo, Holstein cross, indigenous and Red Chittagong cattle of Bangladesh (Bangladesh Journal of Animal Science, 2013)
Low molecular weight chemical compounds or intermediate products of a metabolism or other cellular processes are called metabolites. The objective of the present study was to investigate the variations in the metabolite concentration in the milk from crossbred water Buffalo (B), Holstein cross (H), Indigenous cattle (I) and Red Chittagong Cattle (R) and the relationships among those metabolites. The concentration of citric acid, ? -keto glutaric acid (?-keto GA), orotic acid, pyruvic acid, succinic acid, lactic acid, formic acid, uric acid and propionic acid were measured by using High Performance Liquid Chromatography. Pooled milk samples of nine B, fifteen I and twenty R cows were collected from the research farm of Bangladesh Livestock Research Institute, Savar, Dhaka, Bangladesh. The pooled milk samples of H were collected from twenty five cows of Central Cattle Breeding Station and Dairy Farm, Savar, Dhaka, Bangladesh. All the sampling was done from the morning milking. The samples were preserved by adding bronopol tablet and frozen and stored at -20 °C. Except propionic acid, all the metabolites varied significantly (p